Unveiling The Roles of npcRNA Modulating the Molecular Mechanism of Pathogenic Bacteria Causing Urinary Tract Infections (UTIs) - Enis Mudiliar Rajan; KishanRaj Selva Raju; Suresh V. Chinni; Citartan Marimuthu (Malaysian Journal of Science (MJS), 2025)
Urinary tract infections (UTIs) are among the most prevalent and chronic health problems worldwide, impacting millions of individuals annually and posing a substantial financial burden on healthcare systems. UTIs typically initiate when pathogenic bacteria, originating from the gastrointestinal tract, colonize the urethra or periurethral region. Women are more susceptible to UTIs compared to men because of the differences in female lower urinary tract anatomy and its proximity to reproductive organs. The pathogenic bacteria, which are on the World Health Organization (WHO) priority list and cause both uncomplicated and complicated UTIs, are Escherichia coli (UPEC), Klebsiella pneumoniae, Proteus mirabilis, and Staphylococcus aureus. Different therapeutic approaches are necessary to combat UTIs, as seen by the rise in antibiotic resistance in bacteria. Non-protein coding RNAs (npcRNAs) have emerged as promising candidates for regulating genes involved in bacterial pathogenesis and infection, playing a role in modulating gene expression and host-pathogen interactions. By targeting bacterial virulence factors, biofilm formation, and antibiotic resistance mechanisms, npcRNAs provide a novel approach to disrupting infection pathways while minimizing the risk of resistance development.